Risk communication methods in hip fracture prevention: a randomised trial in primary care - Hudson, Ben (Royal College of General Practitioners, 2011)
BACKGROUND: Treatment acceptance by patients is influenced by the way treatment effects are presented. Presentation of benefits using relative risk increases treatment acceptance compared to the use of absolute risk. It is not known whether this effect is modified by prior presentation of a patient's individualised risk estimate or how presentation of treatment harms by relative or absolute risk affects acceptance. AIM: To compare acceptance of a hypothetical treatment to prevent hip fracture after presentation of the treatment's benefit in relative or absolute terms in the context of a personal fracture risk estimate, and to reassess acceptance following subsequent presentation of harm in relative orabsolute terms. DESIGN AND SETTING: Randomised controlled trial of patients recruited from 10 GPs' lists in Christchurch, New Zealand. METHOD: Women aged ≥50 years were invited to participate. Participants were given a personal 10-year hip fracture risk estimate and randomised to receive information on a hypothetical treatment's benefit and harm in relative orabsolute terms. RESULTS: Of the 1140 women invited to participate 393 (34%) took part. Treatment acceptance was greater following presentation of benefit using absolute terms than relative terms after adjustment forage, education, previous osteoporosis diagnosis, and self-reported risk (OR 1.73, 95% confidence interval [CI] = 1.10 to 2.73, P = 0.018). Presentation of the treatment's harmful effect in relative terms led to a greater proportion of participants declining treatment than did presentation in absolute terms (OR 4.89, 95% CI = 2.3 to 11.0, P<0.001). CONCLUSION: Presentation of treatment benefit and harm using absolute risk estimates led to greater treatment acceptance than presentation of the same information in relative terms.